Avian influenza A virus and Newcastle disease virus mono- and co-infections in birds - Iv. Zarkov (Trakia Journal of Sciences)
The main features of avian influenza viruses (AIV) and Newcastle disease virus (APMV-1), the possibilities for isolation and identification in laboratory conditions, methods of diagnostics, main hosts, clinical signs and virus shedding are reviewed in chronological order. The other part of the review explains the mechanisms and interactions in cases of co-infection of AIV and APMV-1, either between them or with other pathogens in various indicator systems – cell cultures, chick embryos or birds. The emphasis is placed on quantitative data on the virus present mainly in the first ten days following experimental infection of birds, the periods of virus carrier ship and shedding, clinical signs, pathological changes, diagnostic challenges